'I would be rather pleased if the world were to be rid of monks.' Resistance to Cluniac integration in late eleventh- and early twelfth-century France. Issue 1 (1st January 2021) - Vanderputten, Steven
ABSTRACT: This paper takes a bottom-up look at Cluniac integration in the decades either side of the year 1100 in order to explore the diverse institutional, contextual and personal dynamics at play. Taking as its case study the French diocese of Saintes, it charts the transformation of the ecclesia Cluniacensis, the impact on relations with monastic houses in the region and the response by diverse stakeholders. Local groups of monks and their patrons actively participated in the ongoing integration of monastic administration, facilitating the exchange of personnel and know-how. But they also expected these processes to be subject to negotiation and compromise, and when the Cluniacs challenged these expectations the destabilising effect on Saintes society was profound. As such, this study helps to adjust a former narrative that contrasted the Cluniacs' reform of monastic administration in this period with the resistant attitude of individual communities and their local patrons.